A Southern perspective for a social movements' analysis - Camacho De la O, Lorena (2014)
This article establishes a reflection around Boaventura de Sousa Santos thought related to the reality`s social study. The focus is an implementation exercise of some of his categories linked to the social movements’ analysis via a particular case. With this in mind, it pretends to direct the analysis to the social movements (or people in motion as an indigenous claim) discussion, part of the social science’s current debate. A central focus is the contrast of the social movement category with De Sousa`s (2009) proposals of “the sociology of absents”, “the sociology of the emergencies” and the “translation exercise” to reveal the heuristic richness of this thought as an explanation model for actual Costa Rican sociopolitical movements in the contemporaneous systemic social crisis context. Besides, this critical analysis process would help to comprehend the decolonial perspective`s utility and politic potential in particular social contexts studies, for example: Costa Rica.